Peran Guru dalam Upaya Meningkatkan Keterampilan Membaca Siswa Kelas IV di SD Negeri 106810 Sampali - Rambe, Riris Nurkholidah; Utami, Anggi Putri; Salbila, Isal; Handayani, Risma; Bayu, Silvana; Aulia, Usna (Lembaga Yasin AlSys, 2023)
Learning to read faces problems and obstacles. The teacher's role as a facilitator is to facilitate student learning as well as possible by using various strategies, methods and learning resources. The teacher's role in education is to equip students with the central point of science and technology. The purpose of this study was to determine the teacher's role in improving the reading skills of fourth grade students at SDN 106810 Sampali. The method used in this research is a descriptive qualitative method. Based on the results of the research, it can be concluded that there are several types of media used in teaching reading, but students are more interested in media images, for example pop-up books and teaching materials used in teaching reading, namely thematic books. While the efforts that teachers make in improving students' reading skills are by motivating, directing, guiding, providing reading corners, making visits to the library and giving prizes to students whose reading is already fluent and getting used to literacy activities before starting learning so that students like and are interested in reading.